The Effects of Ecolabels and Environmental Regulation on Green Product Development - Murali, Karthik; Lim, Michael K.; Petruzzi, Nicholas C. (Manufacturing and Service Operations Management, 2019)
Problem definition: We develop a framework for studying the impact of voluntary ecolabels and mandatory environmental regulation on green product development among competing firms. Academic/practical relevance: We contribute to the academic literature on environmental quality competition by explicitly accounting for the credibility of environmental claims made by firms, and by exploring the implications for society of two mechanisms used to remedy credibility-related consumer discounting of firms’ self-declared environmental qualities. We draw parallels between our findings and instances of environmental labeling and regulation from industry to highlight the practical implications of our study. Methodology: We use a game-theoretic framework to analyze a consumer-driven model of green product development. Results: Credibility asymmetry drives product differentiation between two competing firms. The less credible firm always adopts external certification, while the more credible firm does so only if its credibility is sufficiently low. Credibility may also determine whether or not the government should intervene. In the absence of an external certifier, the regulator should intervene by imposing a mandatory environmental standard that is decreasing in stringency as the credibility of the more credible firm increases. In the presence of a certifier, the regulator should intervene if neither firm is sufficiently credible, or if consumers do not value environmental stewardship highly. Managerial implications: We identify how and when government should (and should not) intervene to stimulate green product development when competing firms can use self-labels or external certifications to communicate their environmental performance to consumers. We also determine the optimal strategies for the competing firms and external certifiers.